Antibacterial‐nanocomposite bone filler based on silver nanoparticles and polysaccharides. (7th May 2017) - Porrelli, Davide; Travan, Andrea; Turco, Gianluca; Crosera, Matteo; Borgogna, Massimiliano; Donati, Ivan; Paoletti, Sergio; Adami, Gianpiero; Marsich, Eleonora
Abstract: Injectable bone fillers represent an attractive strategy for the treatment of bone defects. These injectable materials should be biocompatible, capable of supporting cell growth and possibly able to exert antibacterial effects. In this work, nanocomposite microbeads based on alginate, chitlac, hydroxyapatite and silver nanoparticles were prepared and characterized. The dried microbeads displayed a rapid swelling in contact with simulated body fluid and maintained their integrity for more than 30 days. The evaluation of silver leakage from the microbeads showed that the antibacterial metal is slowly released in saline solution, with less than 6% of silver released after 1 week. Antibacterial tests proved that the microbeads displayed bactericidal effects toward Staphylococcus aureus, Pseudomonas aeruginosa and Staphylococcus epidermidis, and were also able to damage pre‐formed bacterial biofilms. On the other hand, the microbeads did not exert any cytotoxic effect towards osteoblast‐like cells. After characterization of the microbeads bioactivity, a possible means to embed them in a fluid medium was explored in order to obtain an injectable paste. Upon suspension of the particles in alginate solution or alginate/hyaluronic acid mixtures, a homogenous and time‐stable paste was obtained. Mechanical tests enabled to quantify the extrusion forces from surgical syringes, pointing out the proper injectability of the material. This novel antibacterial bone filler appears as a promising material for the treatment of bone defects, in particular when possible infections could compromise the bone‐healing process. Copyright © 2016 John Wiley & Sons, Ltd.